CYCLICAL CONNECTION BETWEEN TRANSGENERATIONAL TRAUMA, HOSTILE ENVIRONMENT, EPIGENETIC MECHANISMS AND CORTISOL HORMONE - Jefferson, Jadir (Health and Society, 2023)
This narrative review demonstrates the close connection between the impact of traumas experienced across generations, added to an environment of unpredictability during an organism’s life history. The effects of trauma can be passed on to subsequent generations through epigenetic mechanisms and changes in the stress response axis, sensitivity to glucocorticoid receptors, and cortisol release. When associated, they form a line of continuous cause and effect in the life history of the individuals involved and their future generations, favoring new environments of unpredictability and risks that lead to more adverse situations and traumas. Consequently, descendants and nearby people can be impacted by cascading effects related to existing difficulties in environments considered hostile or unpredictable.